A stylistic study of eulogic speeches on the death of Queen Elizabeth II - Ahmed Muhammed, Huda; MingherObied, Iman (Edelweiss Applied Science and Technology, 2024)
This is a quantitative-qualitative, descriptive study . It studies eulogic speeches on the death of Queen Elizabeth II from a stylistic perspective. The study tries to answer the following questions: what are the stylistic devices used and how are they realized ? what are the most prominent stylistic device used in the selected eulogic speeches ? In connection with the study questions, the study aims at : Revealing the stylistic devices that are utilized in the selected eulogic speeches and how they are realized linguistically. Showing the most prominent stylistic devices in the selected eulogic speeches. To achieve the aims of the study, the study follows these procedures : Reviewing the literature review stylistics, stylistic devices, and eulogy, analyzing how the stylistic devices are being employed in the selected eulogic speeches. The model of stylistic devices by Leech and short (2007) is an adapted model. On the basis of the analysis of the present study, the following conclusions are drawn: hyperbole is the most dominant stylistic device used in the selected data followed by metaphor respectively , the stylistic devices are used to create full positive picture about the Queen Elizabeth II in a way that literal meaning could never convey , the stylistic devices are realized in a systematic way to embellish and improve the texts.